Cyclophilin A as a target in the treatment of cytomegalovirus infections - A Abdullah, Ashwaq (Antivir Chem Chemother, 2018)
BACKGROUND: Viruses are obligate parasites that depend on the cellular machinery of the host to regenerate and manufacture their proteins. Most antiviral drugs on the market today target viral proteins. However, the more recent strategies involve targeting the host cell proteins or pathways that mediate viral replication. This new approach would be effective for most viruses while minimizing drug resistance and toxicity. METHODS: Cytomegalovirus replication, latency, and immune response are mediated by the intermediate early protein 2, the main protein that determines the effectiveness of drugs in cytomegalovirus inhibition. This review explains how intermediate early protein 2 can modify the action of cyclosporin A, an immunosuppressive, and antiviral drug. It also links all the pathways mediated by cyclosporin A, cytomegalovirus replication, and its encoded proteins. RESULTS: Intermediate early protein 2 can influence the cellular cyclophilin A pathway, affecting cyclosporin A as a mediator of viral replication or anti-cytomegalovirus drug. CONCLUSION: Cyclosporin A has a dual function in cytomegalovirus pathogenesis. It has the immunosuppressive effect that establishes virus replication through the inhibition of T-cell function. It also has an anti-cytomegalovirus effect mediated by intermediate early protein 2. Both of these functions involve cyclophilin A pathway.